Deskripsi Kemampuan Guru Dalam Menerapkan Dimensi Gotong Royong Pada Pembelajaran Pendidikan Pancasila Di Kelas Vb Sdn 36 Pontianak Kota - Eva Kristi; Hairida Hairida; Siti Halidjah; Rio Pranata (Mathematics Education Study Program, 2025)
This research is to describe the teacher's ability to apply the mutual cooperation dimension to Pancasila education learning in the VB class at SDN 36 Pontianak City. The research method used is the Mix Method with a mixed research form. The research subjects were VB class students and class teachers. The data is in the form of observation results, documentation in the form of photos of the learning implementation and the results of interviews with the VB class teacher. Based on the results of observations, it shows that the implementation of the mutual cooperation dimension is included in the good category with a percentage of 62.49%, the collaboration element is in the very good category with a percentage of 83.33%, the caring element is in the poor category with a percentage of 29.16%, and the sharing element is in the good category with a percentage of 75%. The results of the interview stated that the elements of collaboration and sharing had been implemented very well, while the elements of caring were still lacking. In general, the results of interviews with class teachers stated that the teacher's ability to apply the mutual cooperation dimension had been carried out well.